Propriedades químicas de um latossolo vermelho de cerrado cultivado com algodão sob diferentes preparos e adubações - Mannigel, Anny Rosi; Porto, Simone Maria Altoé; Alves, Marlene Cristina [UNESP]; Filho, Walter Veriano Valério [UNESP] (My University, 2009)
The high rate of mineralization of organic matter on savannah soils, which is reached fi ve times faster than in temperate regions, leads us to the challenge of electing the best system of management that maintains and/or increase it in soil, guaranteeing its quality and sustainability. In this sense the present research aimed to study the effects of green, organic and mineral manure on the chemical properties on the chemical properties of an Oxisol, on Savannah area, cultivated with cotton (Gossypium hirsutum) under conventional tillage and no-tillage in the pasture fi eld (Brachiaria decumbens) for 20 years. The experimental design was a randomized block design with split plots. The main plots consisted of two treatments: conventional tillage and no-tillage, and the subplots of six treatments: control (no fertilizer), mineral fertilizer recommended for the crop, according to the soil chemical analysis, organic fertilizer (cattle manure - 20 t ha-1), organic fertilizer (cattle manure - 20 t ha-1) + 1/2mineral fertilization recommended according to the analysis of soil, green manure-1 (Crotalaria juncea) and green manure-2 (Pennisetum americanum). There were studied the following soil chemical properties: P, OM, pH, K, Ca, Mg, Al, Al + H, S, exchange capacity cations and base saturation. The soil samples for the analysis were performed on layers of 0,00-0,05 m, 0,05-0,10 and 0,10-0,20 m. Then it came the following conclusions: the fertilization interfere in soil chemical properties and the preparation did not interfere, the cattle manure and its association with the mineral fertilizer caused increasing level elements in the soil, Crotalaria juncea and Pennisetum americanum did not infl uence on soil chemical properties.
Chemical properties on a savannah oxisol cultivated with cotton under different tillage and fertilization
Keywords: Cattle Manure; Conventional Tillage; Crotalaria juncea; No-tillage; Pennisetum americanum; Bos; Brachiaria; Crotalaria; Gossypium hirsutum; Pennisetum glaucum; Urochloa brizantha